avnA, a gene encoding a cytochrome P-450 monooxygenase, is involved in the conversion of averantin to averufin in aflatoxin biosynthesis in Aspergillus parasiticus. - Yu, J (1997)
Recent studies have shown that at least 17 genes involved in the aflatoxin biosynthetic pathway are clustered within a 75-kb DNA fragment in the genome of Aspergillus parasiticus. Several additional transcripts have also been mapped to this gene cluster. A gene, avnA (previously named ord-1), corresponding to one of the two transcripts identified earlier between the ver-1 and omtA genes on the gene cluster was sequenced. The nucleotide sequence of the avnA gene contains a coding region for a protein of 495 amino acids with a calculated molecular mass of 56.3 kDa. The gene consists of three exons and two introns. Disruption of the avnA gene in the wild-type aflatoxigenic A. parasiticus strain (SU1-N3) resulted in a nonaflatoxigenic mutant which accumulated a bright yellow pigment. Thin-layer chromatographic studies with six different solvent systems showed that the migration patterns of the accumulated metabolite were identical to those of averantin, a known aflatoxin precursor. Precursor feeding studies with this mutant showed that norsolorinic acid and averantin were not converted to aflatoxin whereas 5'-hydroxyaverantin, averufanin, averufin, versicolorin A. sterigmatocystin, and O-methylsterigmatocystin were converted to aflatoxins. Southern blot analysis of the wild-type strain and avnA-disrupted mutant strain indicated that the avnA gene was disrupted in the mutant strain. A search of the GenBank database for similarity indicated that the avnA gene encodes a cytochrome P-450-type monooxygenase, and it has been assigned to a new P-450 gene family named CYP60A1. We have therefore concluded that the avnA gene encodes a fungal cytochrome P-450-type enzyme which is involved in the conversion of averantin to averufin in the aflatoxin biosynthetic pathway in A. parasiticus.